Projecting Parameters of a Microprofile for a Surface Obtained as a Result of the Thermofrictional Treatment. (2016) - Pokintelitsa, N.; Levchenko, E.
Abstract: The article presents the results of the studies that allow determining the mechanism of forming macro and micro relief of surfaces taking place at termo frictional treatment of parts and ensuring the acquisition of a given accuracy and quality of treatment. It is established that thermo frictional treatment is characterized by complex temperature-deformation processes in the contact zone of the tool and part that are associated with the formation of treatment zones with heating and melting the material. We present complex methods of surface treatment that implement features of thermo frictional and mechanical treatment processes using machine tools by combining preliminary treatment of parts by a disk tool, which has a circular cutting edge and subsequent milling, or grinding and finishing bilateral operations. Thus, after processing we obtain a wavy surface with a random profile, which has a system of parallel grooves and ridges oriented perpendicular to the feeding direction. Parameters of waviness depend on the dynamic characteristics of the machine tool, on the cutting process, and on the use of additional devices. The developed mathematical model of a microprofile allows for determination of the shape and nature of the surface, obtained as a result of complex processing.